2014
DOI: 10.1021/np5007247
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenone C- and O-Glucosides from Cyclopia genistoides (Honeybush) Inhibit Mammalian α-Glucosidase

Abstract: An enriched fraction of an aqueous extract prepared from the aerial parts of Cyclopia genistoides Vent. yielded a new benzophenone di-C,O-glucoside, 3-C-β-d-glucopyranosyl-4-O-β-d-glucopyranosyliriflophenone (1), together with small quantities of a known benzophenone C-glucoside, 3-C-β-d-glucopyranosylmaclurin (2). The isolated compounds showed α-glucosidase inhibitory activity against an enzyme mixture extracted from rat intestinal acetone powder. Compound 2 exhibited significantly (p < 0.05) higher inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Authentic reference standards (purity > 95 %) were sourced from Extrasynthese (eriocitrin, narirutin), Sigma-Aldrich (mangiferin, hesperidin, iriflophenone-3-C-glucoside, scolymoside), Chemos GmbH (isomangiferin), and Phytolab (vicenin-2). Maclurin-3-Cglucoside (95 % purity by LC-MS) and iriflophenone-3-C-glucoside-4-O-glucoside (99 % purity by LC-MS) were previously isolated from C. genistoides [45], while phloretin-3′,5′-di-C-glucoside (94 % purity by LC-MS) was isolated from C. subternata. When no authentic reference standard was available, the compound was quantified in terms of equivalents of the most similar available standard.…”
Section: Phenolic Standards and Solventsmentioning
confidence: 99%
“…Authentic reference standards (purity > 95 %) were sourced from Extrasynthese (eriocitrin, narirutin), Sigma-Aldrich (mangiferin, hesperidin, iriflophenone-3-C-glucoside, scolymoside), Chemos GmbH (isomangiferin), and Phytolab (vicenin-2). Maclurin-3-Cglucoside (95 % purity by LC-MS) and iriflophenone-3-C-glucoside-4-O-glucoside (99 % purity by LC-MS) were previously isolated from C. genistoides [45], while phloretin-3′,5′-di-C-glucoside (94 % purity by LC-MS) was isolated from C. subternata. When no authentic reference standard was available, the compound was quantified in terms of equivalents of the most similar available standard.…”
Section: Phenolic Standards and Solventsmentioning
confidence: 99%
“…Food ingredient extracts from C. subternata exhibit antidiabetic and anti‐obesity properties . In vivo studies demonstrated the glucose‐lowering effect of its major xanthone, mangiferin, while several other phenolic compounds in C. subternata are postulated to contribute towards its antidiabetic and anti‐obesity properties . Cyclopia subternata extract is therefore an excellent functional ingredient to include in a reduced‐sugar beverage.…”
Section: Introductionmentioning
confidence: 99%
“…subternata , unpublished results), eriocitrin (Extrasynthese), hesperidin (Sigma-Aldrich), vicenin-2 (Phytolab, Germany), isorhoifolin (Extrasynthese), scolymoside (isolated from C . subternata , unpublished results), and iriflophenone-3- C -β-D-glucoside-4- O -β-D-glucoside (isolated from Cyclopia genistoides [ 49 ]).…”
Section: Methodsmentioning
confidence: 99%